LECTURER’S AND STUDENTS’ TALK IN THE CLASSROOM INTERACTION OF INTERPRETIVE READING CLASS - Fitri Nurdianingsih; Sabila Nur Falah Ardiana; Dani Dani (IKIP Siliwangi, 2023)
The objectives of this study is to analyse the classroom interaction in Interpretive Reading Class Activities by describing its communication contents and patterns of teaching and learning interaction. This study was carried out through a case study. It was conducted in second semester students of English Education Study Program at IKIP PGRI Bojonegoro. The participant were 22 students. The data were collected through classroom observation and interview for the lecturer. The data were analyzed by using the interaction analysis system from Flanders (1970). The results showed that there were some types of interaction between the teacher and the students in the classroom, namely: questioning, accepting or using ideas of people, encouraging, directing, lecturing, and accepting the feeling. From the observation, the teacher not only used English, but also used Indonesian as a communication tool to interact with the students Keywords: Classroom Interaction; Lecturer Talk; Students Talks; Interpretive Reading